16th Symposium of the International Society of Biomechanics in Sports
Abstracts of the reports held at the 16th Symposium of the International Society of Biomechanics in Sports, which was held in Konstanz in July 21-25, 1998. The reports were held in the following fields: 1. Pure and Applied Sports Biomechanics 2. Modeling, Simulation, Optimization in Sports Biomechanics 3. Applied Methods and Instrumentation 4. Biomechanics of the Musculo-Skeletal System 5. Biomechanics of Training and Sports Equipment 6. Biomechanics of Injuries, Orthopedics, and Rehabilitation in Sports